2022
DOI: 10.3390/nu14050937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Whole Brown Bean and Its Isolated Fiber Fraction on Plasma Lipid Profile, Atherosclerosis, Gut Microbiota, and Microbiota-Dependent Metabolites in Apoe−/− Mice

Abstract: The health benefits of bean consumption are widely recognized and are largely attributed to the dietary fiber content. This study investigated and compared the effects of whole brown beans and an isolated bean dietary fiber fraction on the plasma lipid profile, atherosclerotic plaque amount, gut microbiota, and microbiota-dependent metabolites (cecal short-chain fatty acids (SCFAs) and plasma methylamines) in Apoe−/− mice fed high fat diets for 10.5 weeks. The results showed that both whole bean and the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The expression of Bifidobacterium and Lactobacillus was significantly increased after CDFC intervention. Legume dietary fiber was reported to increase the relative abundance of Bifidobacterium in the feces of mice [ 49 ]. The intake of dextran resulted in a dose-dependent decrease in Bacteroides and an increase in Lactobacillus and Bifidobacterium [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Bifidobacterium and Lactobacillus was significantly increased after CDFC intervention. Legume dietary fiber was reported to increase the relative abundance of Bifidobacterium in the feces of mice [ 49 ]. The intake of dextran resulted in a dose-dependent decrease in Bacteroides and an increase in Lactobacillus and Bifidobacterium [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…100 For example, kidney bean NSPs (33.60 g kg −1 mice weight) could increase the relative abundance of the Actinobacteria and Bacteroidetes phyla in the intestine of mice, while the ratio of Firmicutes/Bacteroidetes decreased, promoting the production of short chain fatty acids (SCFAs) (Table 6). 101 A similar study also showed that red kidney bean NSPs (1% w/v, NSPs/medium) significantly pro-moted beneficial intestinal flora, especially Bifidobacterium and Lactobacillus, and increased the concentration of SCFAs, while inhibiting the formation of E. coli biofilm by 79%. 17 The differences in the growth performance between beneficial and enteric bacteria by kidney bean NSPs may rely on the production of glycolytic enzymes.…”
Section: Reviewmentioning
confidence: 78%
“…In response to these challenges and the increasing demand for high-quality marine products, it is imperative to develop sustainable health management strategies for aquaculture [ 14 ]. These strategies should not only focus on growth performance but also provide effective solutions for environmental stressors, such as ammonia-nitrogen stress [ 15 ], thereby making significant contributions to global food security. With projections indicating a more intensive form of aquaculture by 2050, widespread concerns have arisen regarding the immune capabilities of aquatic animals and their resilience to environmental stressors [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%